Variasi Genetik Gen LMP-1 HHV 4 berdasarkan Analisis RFLP Secara In silico: Genetic Variation of LMP-1 HHV 4 Gene based on In silico RFLP Analysis - Rahma Windi Astuti; Khoirunnisa; Eka Resi Kurniawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Human Herpesvirus 4 (HHV-4), also known as Epstein-Barr virus (EBV), is a member of the herpes virus family that has significant genetic variation. Molecular studies show that this variation can occur in genes that code for capsid proteins, DNA-binding proteins, and transcription-regulating proteins. In silico methods are used to determine mutations and genetic variations. The purpose of this study was to explore genetic variability in the LMP-1 HHV 4 gene sequence from NCBI PopSet 2581709082 using RFLP in silico. Restriction enzyme screening using restriction enzyme digest of DNA sites. RFLP in silico using the Benchling site. Genetic variability using the MEGA 11 application. The results obtained in silico screening of restriction enzymes and RFLP showed arelationship between PopSet 2581709082 genetic variation and HHV 4 LMP-1 genes, marked by the presence of five alleles, namely A1, A2, A3, A4, and A5.